2007
DOI: 10.1016/j.marpolbul.2006.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Luminex detection of fecal indicators in river samples, marine recreational water, and beach sand

Abstract: Research to understand and remediate coastal pollution is moving toward a multitiered approach in which traditional enumeration of fecal indicators is accompanied by molecular analysis of a variety of targets. Technology that rapidly detects multiple microbial contaminants would benefit from such an approach. The Luminex ® 100™ system is a suspension array that assays multiple analytes rapidly in a single well of a microtiter plate. The ability of the system to simultaneously detect multiple fecal indicating b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(31 citation statements)
references
References 60 publications
0
31
0
Order By: Relevance
“…and pathogenic bacteria such as Shigella spp. in a multiplex format (21). In brief, the extracted DNA is marked with probes, and a detection system determines the overall concentration of the target microbes.…”
Section: Rapid Testing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…and pathogenic bacteria such as Shigella spp. in a multiplex format (21). In brief, the extracted DNA is marked with probes, and a detection system determines the overall concentration of the target microbes.…”
Section: Rapid Testing Methodsmentioning
confidence: 99%
“…Experiments using natural waters found that the methodology worked best on river water samples. The targets were not as concentrated in beach water and sand; therefore, group-specific primers were developed to optimize the technique for these natural waters (21). Initial results indicated that the system could detect Enterococcus spp., but quantities were often quite different from those obtained by culture methods (21).…”
Section: Rapid Testing Methodsmentioning
confidence: 99%
“…Luminex beadarrays have been developed for detecting microbial pathogens from clinical (e.g. Bandyopadhyay et al 2007) and environmental (Baums et al 2007) samples. Applications of this technology have also been used to determine bacteria and phytoplankton abundances from the marine environment (Ellison & Burton 2005, Scorzetti et al 2009, Mayali et al 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Even if the functional inventory (DNA level) of the bacterial communities at the dumping site is significantly lower, the transcription of for instance pollutant specific genes might be enhanced instead. Environmental pollution, resulting from organic, heavy metal antibiotic contamination, was reported to influence gene regulation in previous studies (Baums et al, 2007;Busenlehner et al, 2003;Diaz and Prieto, 2000). While organic pollutants might be used as an alternative energy source (Gibson et al, 1988;Kanaly and Harayama, 2000), heavy metal contamination results in the up-regulation of transporter genes (Hu et al, 2005) or a chemical transformation of the substances, as in the case of mercury contamination (Nascimento and Chartone-Souza, 2003).…”
Section: Discussionmentioning
confidence: 92%